Pertempuran Laut Jawa 1942: Kekalahan Koninklijke Marine Atas Imperial Japanese Navy - Jonathan Abrianto (PANALUNGTIK, 2025)
This paper examines the role and strategic capacity of the Royal Netherlands Navy (Koninklijke Marine) during the Japanese invasion of the Dutch East Indies in 1941–1942. Employing historical research methods, this study synthesizes primary and secondary sources to analyze the operational performance of the Koninklijke Marine within the Allied naval framework. Findings indicate that by the early twentieth century, the Royal Netherlands Navy remained relatively small and technologically limited compared to both its Allied partners and its principal adversary, the Imperial Japanese Navy. Consequently, the Koninklijke Marine relied heavily on cooperation with larger Allied fleets, particularly those of the United Kingdom and the United States, to counter Japanese expansion. Despite these collaborative efforts, Allied naval forces in the region were decisively defeated, most notably in the Battle of the Java Sea, where they suffered overwhelming losses. The analysis demonstrates that the Allies—outnumbered, outgunned, and tactically outmanoeuvred—were unable to prevent Japan from achieving maritime dominance and subsequently occupying the Dutch East Indies.